The Platformization of Culture: Webtoon Platforms and Media Ecology in Korea and Beyond - Cho, Heekyoung (The Journal of Asian studies, 2021)
This article examines the webtoon (wept'un)—a term coined in Korea to refer to webcomics—which is arguably the most pervasive and powerful form of digital serial production in twenty-first-century Korea. Webtoons have developed by utilizing various potentials that the digital platform offers, such as open solicitation, (partial) free web/mobile distribution, profit from advertisement and page viewing, and transmedia production. As a new cultural medium, the webtoon is thus inseparable from its platform and organically tied to its distinctive platform ecology, which is different from the ecosystems that other (global) mega-platforms create. Engaging with the insights from recent studies of platforms and utilizing empirical media analysis, I argue that Korean webtoon platforms demonstrate the continuing and intensifying dependency of art on platforms—a process that I call “the platformization of culture”—and that this specific type of platformization is reinforced by what I call “the artist incubating system.” The case of webtoon platforms reveals a number of telling aspects of media ecosystems for art production in the digital age—aspects that are spreading and expanding to various fields of art.